(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the formation and development of the education system in the Fergana Valley during the 1920s-1930s, the Soviet government’s policy in this field, and the process of establishing the first higher education institution in the region — Fergana State Pedagogical Institute. The analysis highlights how the Soviet authorities used education not only to increase literacy but also as a means of instilling communist ideology among the local population. The article examines the social, political, and cultural aspects of the reforms, showing both their positive and negative sides. Negative consequences such as increased political control and the weakening of religious education were also observed. Therefore, a comprehensive analysis of this period plays a crucial role in fully understanding the historical significance of the changes in education. Additionally, the role and importance of the Fergana State Pedagogical Institute in training pedagogical personnel in the region are emphasized.